"At the brink of a vision": epiphany in the short stories of Katherine Mansfield and Nadine Gordimer - Pawlicki, Marek (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The main aim of the article is to discuss the influence of Katherine Mansfield`s prose on the short stories of Nadine Gordimer. The article starts with an overview of short story criticism, concentrating on the theories of the modernist short story by Clare Hanson and Dominic Head.
Keywords: Mansfield, Katherine (pseud.); Mansfield Murry, Kathleen (1888-1923); Gordimer, Nadine (1923-2014); the modernist short story